The ‘Kelingai Motif’ in Iban’s tattoo motif : a case study of Kampung Gayau Ulu Pantu, Sri Aman Sarawak / Gladys Tagie, Nurul Shima Taharuddin and Noor Aileen Ibrahim - Gladys, Tagie; Nurul Shima, Taharuddin; Noor Aileen, Ibrahim (Universiti Teknologi MARA, Perak, 2020)
This research is conducted on core problem that had occurred on ‘Kelingai’ motif (cultural form) among new modern young generation. ‘Kelingai’ motif is a symbol of indigenous culture Iban people in Sarawak, but ironically has many motives ‘Kelingai’ intertwined with a modern motif and has been widely used by young people today. This generation seems to take for granted for the beauties of ‘Kelingai’ motifs that they leave behind their original motifs of tattoo founded by their ancient generation before in valuable traditional art. ‘Kelingai’ motif represent its own meaning according to geographical factor and tattoo wearer’s belief. This big question aroused deep interest for the researcher to explore and reveal the secret wold of ‘Kelingai’ motif of tattoo. The research had been conducted among Kampung Gayau’s resident who comes with their tattoo at all age levels. This research basically based on well-known theories, Erwin Panofsky Theory. This theory will reveal the meaning of ‘Kelingai’ history through it pproaches such as in style, type and symbol domains in the theory. These domains help us to know better about the history of ‘Kelingai’ motif in Kampung Gayau, explicity and also to Iban’s society internationally as a group of people who nourishing their ancestors’ life value into their young generation in modernization and globalization